Harmful Effects of Smoking Cannabis: A Cerebrovascular and Neurological Perspective - Archie, Sabrina Rahman; Cucullo, Luca (Frontiers in Pharmacology, 2019)
Apart from being used as a medicine, cannabis or marijuana is the most widely abused recreational drug all over the world. The legalization and decriminalization of cannabis in Canada and various states of USA may be the underlying reason of the widespread popularity of it among young population. Various studies have reported about the relationship between cannabis use and different detrimental effects like cardiovascular, cerebrovascular and neurological complications among different age groups. Specifically, the young population is getting adversely affected by this, harmful yet, readily accessible recreational drug. Although the mechanism behind cannabis mediated neurological and cerebrovascular complications has not been elucidated yet, the results of these studies have confirmed the association of these diseases with cannabis. Given the lack of comprehensive study relating these harmful complications with cannabis use, the aim of this article is to evaluate and summarize current studies on cannabis consumption and cerebrovascular/neurological diseases along with the leading toxicological mechanisms.